2016
DOI: 10.1186/s12938-016-0289-4
|View full text |Cite
|
Sign up to set email alerts
|

Movement visualisation in virtual reality rehabilitation of the lower limb: a systematic review

Abstract: BackgroundVirtual reality (VR) based applications play an increasing role in motor rehabilitation. They provide an interactive and individualized environment in addition to increased motivation during motor tasks as well as facilitating motor learning through multimodal sensory information. Several previous studies have shown positive effect of VR-based treatments for lower extremity motor rehabilitation in neurological conditions, but the characteristics of these VR applications have not been systematically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 61 publications
(39 reference statements)
0
34
0
4
Order By: Relevance
“…Biofeedback uses physiological sources like electromyograms to provide patients with real-time visual or auditory signals about their motor activity (Huang et al, 2006). Ultimately arm movements can be visualized and augmented using VR representations (Ballester Rubio et al, 2015b;Ferreira dos Santos et al, 2016).…”
Section: Implicit Feedback/knowledge Of Performancementioning
confidence: 99%
“…Biofeedback uses physiological sources like electromyograms to provide patients with real-time visual or auditory signals about their motor activity (Huang et al, 2006). Ultimately arm movements can be visualized and augmented using VR representations (Ballester Rubio et al, 2015b;Ferreira dos Santos et al, 2016).…”
Section: Implicit Feedback/knowledge Of Performancementioning
confidence: 99%
“…Previous research has shown motor adaptation in upper limb experiments in the presence of an avatar (Bourdin et al, 2019). However, studies about gait kinematics are still needed to understand the specific components of virtual reality immersion and their possible benefits (Ferreira dos Santos et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…B. Hinweise, dass die bewegungssynchrone Darstellung eines Körpers in virtueller Umgebung (Avatar) zusätzliche Effekte bewirkt, die über den rein motivationalen Aspekt einer spielerischen Umgebung mit Zielerreichung hinausgeht. Erste Ansätze einer Klassifizierung der verschiedenen Umgebungen wurden vorgestellt [26]. Insgesamt muss davor gewarnt werden, dass "bunter" und "ausgefeilter" gerade bei kognitiv eingeschränkten Patienten nicht unbedingt auch besser wirksam sein muss.…”
Section: Verbesserung Von Ganggeschwindigkeit Und Gehstreckeunclassified